Analysis of Factors Influencing Accuracy of Volume Flow Measurement in Dialysis Access Fistulas Based on Duplex Ultrasound Simulation. (October 2019) - Zierler, R. Eugene; Leotta, Daniel F.; Sansom, Kurt; Aliseda, Alberto; Anderson, Mark D.; Sheehan, Florence H.
Objective: We developed a duplex ultrasound simulator and used it to assess accuracy of volume flow measurements in dialysis access fistula (DAF) models. Methods: The simulator consists of a mannequin, computer, and mock transducer. Each case is built from a patient's B-mode images that are used to create a 3-dimensional surface model of the DAF. Computational fluid dynamics is used to determine blood flow velocities based on model vessel geometry. The simulator displays real-time B-mode and color-flow images, and Doppler spectral waveforms are generated according to user-defined settings. Accuracy was assessed by scanning each case and measuring volume flow in the inflow artery and outflow vein for comparison with true volume flow values. Results: Four examiners made 96 volume flow measurements on four DAF models. Measured volume flow deviated from the true value by 35 ± 36%. Mean absolute deviation from true volume flow was lower for arteries than veins (22 ± 19%, N = 48 vs. 58 ± 33%, N = 48, p < 0.0001). This finding is attributed to eccentricity of outflow veins which resulted in underestimating true cross-sectional area. Regression analysis indicated that error in measuring cross-sectional area was a predictor of error in volume flow measurement (β = 0.948, p < 0.001). Volume flow error was reduced from 35 ± 36% to 9 ± 8% ( p < 0.000001) by calculating vessel area as an ellipse. Conclusions: Duplex volume flow measurements are based on a circular vessel shape. DAF inflow arteries are circular, but outflow veins can be elliptical. Simulation-based analysis showed that error in measuring volume flow is mainly due to assumption of a circular vessel.